Urgensi Fiqh Anti-Korupsi dan Metode Pengembangannya - M. Tamyiz Muharrom (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2006)
Since 1995, Indonesia has been placing itself in the big the most corrupt country. This worldly bad prestation continues in its yearly life sine. This phenomena looked as social irony, because Indonesia is religious country. Almost Indonesian are muslim. Corruption in this country is not only law phenomena, but also becomes Indonesian society culture. Almost social space was influenced by corruption viruses, in politic, bureaucracy, education area, economy even in the religion area. Moreover, corruption is not ordinary crime, but humanity crime. The corruption phenomenon are happen in global area, national, and also local area. The following article tries the Islamic law perspective against corruption.